Rembrandt Seen Through Jewish Eyes The Artist's Meaning to Jews from His Time to Ours - Knotter, Mirjam; Schwartz, Gary (Amsterdam University Press, 2024)
The earliest painting by Rembrandt whose owner is documented depicts the prophet Balaam, on his way to blessing Israel. The man who bought it was a Sephardi Jew in the service of Cardinal Richelieu of France. The first known buyer of an etching plate by Rembrandt, depicting Abraham Dismissing Hagar and Ishmael, was a Sephardi Jew of Amsterdam. Seen through their eyes, Rembrandt was the creator of images with a special meaning to Jews. They have been followed through the centuries by Jewish collectors, Jewish art historians, Jewish artists who saw their own deepest concerns modelled in his art and life, and even prominent rabbis, one of whom said that Rembrandt was a Tzadik, a holy man blessed by God. This book is the first study in depth of the potent bond between Rembrandt and Jews, from his time to ours, a bond that has penetrated the image of the artist and the people alike.